Low-alloy high-hardenability ultrahigh-strength steel and preparation method thereof

By adjusting chemical composition and adding trace elements, forming fine diffusion reinforced phases and optimizing the quenching process, the problem of insufficient strength and hardenability of ultra-high-strength steel in the existing technology is solved, and high strength, high hardenability and low cost are achieved Ultra-high strength steel produced.

CN119433356AActive Publication Date: 2025-02-14XIAN GANGYAN SPECIAL ALLOY CO LTD

Patent Information

Application Number
CN202411597894.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-14
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The prior art is difficult to provide high-strength and high-hardening ultra-high-strength steels while maintaining low cost production.

Method used

By adjusting chemical composition, add trace Si, Mn, Cr, and Ni elements, and add trace Al, Ti, and V elements to form a fine diffusion reinforced phase to prevent grain boundaries from moving and grain growth. At the same time, optimize by adding Mo and B elements Quenching process improves martensite formation and hardenability.

Benefits of technology

Achieved ultra-high strength with tensile strength not less than 1600MPa, yield strength not less than 1300MPa, elongation ≥10%, impact work ≥50J, fracture toughness K1c ≥110MPa*m0.5 and hardenability ≥J46-50 steel and reduce production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005127438930000011
    Figure HDA0005127438930000011
  • Figure HDA0005127438930000012
    Figure HDA0005127438930000012
  • Figure HDA0005127438930000021
    Figure HDA0005127438930000021
Patent Text Reader

Abstract

The low-alloy high-hardenability ultrahigh-strength steel comprises the following chemical components in percentage by mass: 0.29 to 0.33 percent of C, 1.30 to 1.60 percent of Mn, 1.30 to 1.60 percent of Si, 1.10 to 1.40 percent of Cr, 0.40 to 0.50 percent of Ni, 0.30 to 0.50 percent of Mo, 0.08 to 0.15 percent of V, less than or equal to 0.20 percent of Cu, 0.02 to 0.06 percent of Ti, 0.001 to 0.005 percent of B, 0.01 to 0.06 percent of Al, less than or equal to 0.0060 percent of S, less than or equal to 0.013 percent of P and the balance of Fe. On the basis of 30CrMnSiA, a trace amount of alloy elements Ni, Mo, V, Ti, B and Al are added, and the high-strength steel with the strength of 1600 MPa is obtained in cooperation with a production process; and meanwhile, excellent hardenability is obtained, and the steel can be used as a civil structural material and also can be suitable for the military industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-strength steel and relates to a low-alloy high-hardenability ultra-high-strength steel and a preparation method thereof. Background Art

[0002] Alloy structural steel 30CrMnSi: GB / T3077 belongs to hypoeutectoid steel, with tensile strength ≥1080MPa and yield strength ≥835MPa. This material usually needs to be tempered before use: quenching + high temperature tempering, chemical heat treatment, flame quenching or high frequency quenching and other heat treatments to make the steel obtain uniform troostite, bainite or ultra-fine pearlite structure with good comprehensive mechanical properties. The above structures can obtain higher strength and appropriate toughness and plasticity due to the principle of fine grain strengthening. Therefore, 30CrMnSi material is suitable for civilian fields and national defense and military fields with low strength requirements.

[0003] However, with the advancement and development of technology, not only is the demand for ultra-high-strength steel increasing, but the performance requirements are also becoming higher and higher, while at the same time reducing production costs. Summary of the invention

[0004] The problem solved by the present invention is to provide a low-alloy high-hardenability ultra-high strength steel and a preparation method thereof, wherein the strength is not less than 1600MPa, the hardenability is not less than J46-50, and the steel can be produced at low cost.

[0005] In order to achieve the purpose of the present invention, the present invention provides the following technical solutions:

[0006] A low alloy high hardenability ultra-high strength steel, whose chemical composition, in terms of mass percentage, is:

[0007] C: 0.29~0.33%, Mn: 1.30~1.60%, Si: 1.30~1.60%, Cr: 1.10~1.40%, Ni: 0.40~0.50%, Mo: 0.30~0.50%, V: 0.08~0.15%, Cu: ≤0.20%, Ti: 0.02~0.06%, B: 0.001~0.005%, Al: 0.01~0.06%, S: ≤0.0060%, P: ≤0.013%, and the balance is Fe.

[0008] Further, in terms of mass percentage, its chemical composition is:

[0009] C: 0.29~0.30%, Mn: 1.30~1.60%, Si: 1.36~1.60%, Cr: 1.24~1.40%, Ni: 0.45~0.50%, Mo: 0.30~0.46%, V: 0.08~0.15%, Cu: ≤0.20%, Ti: 0.02~0.041%, B: 0.001~0.0027%, Al: 0.02~0.06%, S: ≤0.0060%, P: ≤0.013%, and the balance is Fe.

[0010] Further, in terms of mass percentage, its chemical composition is:

[0011] C: 0.29~0.33%, Mn: 1.30~1.42%, Si: 1.30~1.54%, Cr: 1.10~1.33%, Ni: 0.40~0.47%, Mo: 0.43~0.50%, V: 0.08~0.10%, Cu: ≤0.20%, Ti: 0.023~0.06%, B: 0.003~0.005%, Al: 0.01~0.06%, S: ≤0.0060%, P: ≤0.013%, and the balance is Fe.

[0012] Further, in terms of mass percentage, its chemical composition is:

[0013] C: 0.31~0.33%, Mn: 1.44~1.60%, C: 0.29~0.33%, Mn: 1.30~1.42%, Si: 1.40~1.52%, Cr: 1.20~1.31%, Ni: 0.40~0.46%, Mo: 0.43~0.50%, V: 0.08~0.12%, Cu: ≤0.20%, Ti: 0.042~0.052%, B: 0.001~0.003%, Al: 0.01~0.06%, S: ≤0.0060%, P: ≤0.013%, and the balance is Fe.

[0014] The present invention also provides a method for preparing the low-alloy high-hardenability ultra-high strength steel, comprising the following operations:

[0015] S1 Electric Arc Furnace Melting

[0016] Before charging, lime is laid on the bottom of the electric arc furnace, and then the charge is loaded; the charge includes carbon steel, ferrochrome, ferronickel, and ferromolybdenum, with a carbon content of ≥0.6%;

[0017] After the furnace is loaded, it is sent to electric melting. Fluorite is added to make slag during the material smelting process. The whole process is to make foam slag and submerged arc operation, and the slag flow operation is adopted to ensure that the slag volume in the furnace is 3-5%; after full melting, it enters the oxidation period and oxygen is blown for dephosphorization;

[0018] The temperature of the smelting process is controlled between 1550 and 1670°C, the current is ≤60000A, and the smelting time is 2 to 4 hours;

[0019] After smelting, the steel is tapped at a temperature of 1650-1670°C. The steel composition requirements by mass fraction are: C≤0.1%, P≤0.002%, Cu≤0.10%;

[0020] S2 refining furnace smelting

[0021] When the electric arc furnace is tapped to the refining furnace, Al material, ferrosilicon, ferromanganese, pre-melted slag are added along the flow, and then slag-making materials are added; Ar protection is used during the steel connection process of the refining furnace, and the flow rate is ≥80NL / min;

[0022] Then add C powder and aluminum particles for deoxidation at one time, close the furnace door; then quickly raise the temperature to above 1620℃, and enter the refining stage after the slag turns white;

[0023] The refining temperature is 1620-1650°C, and the refining time is not less than 40 minutes. During the refining period, samples are taken for component analysis, and ferromolybdenum, ferrovanadium, ferroboron and materials required to make up the components are added according to the analysis results, and the Ar gas stirring is maintained at 30-50NL / min.

[0024] When the refining time is sufficient and the composition is qualified, the refining is completed. After the temperature is raised to 1670-1700℃, the bag enters the vacuum degassing furnace;

[0025] S3 Vacuum Degassing

[0026] The vacuum degree of vacuum degassing is ≤67Pa, the pressure holding time is not less than 20min, the Ar gas flow rate is controlled at 10~40NL / min, and the vacuum can be broken after the pressure holding time is sufficient;

[0027] When the temperature is controlled to 1560-1580℃, the ladle is hung to cast the electrode;

[0028] After the electrode is cast, the mold is cooled, and after the mold is cooled for 12 hours, the electrode is demoulded to obtain the electrode;

[0029] S4 Electroslag Remelting

[0030] After the oxide skin is removed from the electrode surface, the electrode is electroslag remelted. The amount of pre-melted slag is 3-5% by mass ratio. Ar gas protection is used throughout the electroslag remelting process. The remelting rate is 5-7kg / min. After the electrode is remelted, it is annealed.

[0031] S5 Forging

[0032] The steel ingot obtained by electroslag remelting is heated at 1190-1230°C for 2-4 hours, and then forged after being taken out of the furnace;

[0033] The forging ratio is required to be no less than 7, the initial forging temperature is ≥1120℃, and the final forging temperature is ≥850℃.

[0034] S6 Heat Treatment

[0035] After forging, the heat treatment system of normalizing, quenching and tempering is carried out in sequence; during normalizing, the temperature is 920±10℃, kept warm for 3~5h and then air-cooled; during quenching, the temperature is 930±10℃, kept warm for 3~5h and then oil-cooled; during tempering, the temperature is 260±10℃, kept warm for 2~10h and then air-cooled.

[0036] Furthermore, the charge includes carbon scrap steel and CrNiMo return steel, ferrochrome, ferronickel and ferromolybdenum, and the carbon content is 0.70% of the charge mass; the lime paved on the furnace bottom is 0.020-0.030% of the charge mass.

[0037] Furthermore, during smelting in the refining furnace, the slag-making materials include pre-melted slag, lime and fluorite; in terms of mass ratio, the amount of pre-melted slag is 1.0-1.60% of the molten steel, the amount of lime is 1.0-1.50% of the molten steel, and the ratio of lime to fluorite is 4-5:1.

[0038] Compared with the prior art, the present invention has the following beneficial technical effects:

[0039] The low-alloy high-hardenability ultra-high-strength steel provided by the present invention has a high-strength steel tensile strength Rm≥1600MPa, a yield strength Rp0.2≥1300MPa, an elongation A≥10%, an impact energy Aku≥50J, a fracture toughness K1c≥110MPa*m0.5, and a hardenability ≥J46-50. It is a low-alloy, low-cost, high-hardenability ultra-high-strength steel; the ultra-high-strength steel can be used not only as a civilian structural material, but also in military applications.

[0040] The low-alloy high-hardenability ultra-high-strength steel provided by the present invention is based on 30CrMnSiA, and the strength is improved by increasing trace Si, Mn, Cr, and Ni elements and utilizing the substitution solid solution strengthening principle; by adding trace Al, Ti, and V elements, they preferentially combine with N and C atoms dissolved in the alloy liquid during the solidification process to form fine dispersed strengthening phases AlN, TiN, and V4C3, which exist in the matrix to hinder and inhibit the movement of grain boundaries and grain growth in the steel, refine the grain size, and increase strength and toughness; and the inclusion content is increased, and finally the tensile strength is not less than 1600MPa. Compared with the tensile strength of 1080MPa of 30CrMnSiA, the tensile strength of the present invention is significantly improved;

[0041] The low-alloy high-hardenability ultra-high strength steel provided by the present invention also hinders the diffusion of C atoms and the formation of pearlite during quenching by adding trace amounts of Mo and B elements, thereby creating favorable conditions for the formation of martensite and improving the hardenability.

[0042] The low-alloy high-hardenability ultra-high-strength steel provided by the present invention uses as little expensive and scarce resources as possible, such as nickel, cobalt, tungsten, and molybdenum. The total content of the precious metals Ni, Mo, and V used is less than 1%, and the smelting process is a cheap electric arc furnace + refining furnace + electric slag remelting; therefore, the production cost of the ultra-high-strength steel is reduced while ensuring the quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is the hardenability test curve of the ultra-high strength steel of the present invention.

[0044] Figure 2 This is the grain size test result of the ultra-high strength steel of the present invention.

[0045] Figure 3 This is the inclusion detection result of the ultra-high strength steel of the present invention. DETAILED DESCRIPTION

[0046] The present invention is further described in detail below in conjunction with the embodiments, which are intended to explain the present invention rather than to limit it.

[0047] The low-alloy high-hardenability ultra-high-strength steel provided by the present invention is prepared on the basis of 30CrMnSiA by increasing trace Si, Mn, Cr and Ni elements and utilizing the substitution solid solution strengthening principle to improve strength; by adding trace Al, Ti and V elements, they preferentially combine with N and C atoms dissolved in the alloy liquid during the solidification process to form fine dispersed strengthening phases AlN, TiN and V4C3, which exist in the matrix to hinder and inhibit the movement of grain boundaries and grain growth in the steel, thereby refining the grain size.

[0048] Example 1

[0049] A low alloy high hardenability ultra-high strength steel, the chemical composition of which, in terms of mass percentage, includes:

[0050] C: 0.30%, Mn: 1.30%, Si: 1.36%, Cr: 1.24%, Ni: 0.45%, Mo: 0.46%, V: 0.08%, Cu: ≤0.010%, Ti: 0.041%, B: 0.0027%, Al: 0.02%, S: 0.002%, P: 0.004%, and the balance is Fe.

[0051] The method for preparing the low-alloy high-hardenability ultra-high strength steel comprises the following steps:

[0052] S1 Electric Arc Furnace Melting

[0053] A. Select the charge according to the composition requirements. The charge mainly consists of carbon scrap steel (50%-70%) and CrNiMo return steel (30-50%), ferrochrome, ferronickel and ferromolybdenum, with a carbon content of 0.70%;

[0054] Before loading the furnace, 750kg of lime is laid on the bottom of the furnace, and then scrap steel is loaded for electric melting. The loading capacity is 30t. The laid lime can make the molten steel slag alkaline, which has a dephosphorization effect.

[0055] B. During the material smelting process, 375kg of fluorite is added, the slag making amount is 3.75%, and the whole process is a submerged arc operation for foam slag (oxygen and carbon powder are sprayed at the point where the arc is generated to increase the viscosity of the liquid slag and then transform it into foam slag), and a slag flow operation is used; after full melting, it enters the oxidation period and oxygen is blown for dephosphorization;

[0056] The current is controlled at ≤60000A, the melting time is 2-4h, and the melting process temperature is controlled between 1550-1670℃;

[0057] C. Steel composition control C: 0.070%, P≤0.001%, Cu≤0.10%. Steel tapping temperature is 1668℃.

[0058] S2 refining furnace smelting

[0059] A. During the steel tapping process of the electric arc furnace, 30kg Al cake, 150kg silicon-manganese alloy and 150kg pre-melted slag are added; during the steel tapping process of the refining furnace, the Ar flow rate is 87NL / min.

[0060] B. Add slag-making materials into the refining furnace, including 600kg lime, lime: fluorite = 5:1, after steel tapping is completed; then add 60kg C powder, 60kg calcium carbide, and 30kg aluminum particles at one time, close the furnace door for diffusion deoxidation.

[0061] C. After adding slag-making materials and deoxidizer, the temperature is quickly raised to 1633℃, and the slag becomes white before entering the refining stage. The refining temperature is 1633℃ and the refining time is 45min;

[0062] During the refining period, samples were taken for composition analysis. Based on the analysis results and wiring calculations, 10 kg of carbon powder, 65 kg of ferromanganese, 25 kg of ferrosilicon, 60 kg of ferrochrome, 29 kg of ferronickel, 2 kg of ferromolybdenum, 20 kg of ferrovanadium, 3.1 kg of sponge titanium and 1.5 kg of ferroboron were added.

[0063] D. The refining time is sufficient, the composition is qualified, the refining is completed, the temperature is raised to 1688℃, and the bag enters the vacuum degassing furnace.

[0064] S3 Vacuum Degassing

[0065] The vacuum degree of vacuum degassing is 33Pa, the pressure holding time is 20min, the Ar gas flow rate is 30NL / min, and the vacuum is broken after the pressure holding time is sufficient.

[0066] The measured temperature is 1563℃, the ladle casting electrode has the size of φ530*L, where L is the length, mm.

[0067] After the electrode casting is completed, the mold is cooled for 12 hours and the electrode is obtained after demoulding.

[0068] S4 Electroslag Remelting

[0069] The electrode surface is descaled and then electroslag remelted.

[0070] The amount of pre-melted slag is 180 kg. The components of the pre-melted slag are, by mass percentage, CaF2: 37.5%, CaO: 21.7%, MgO: 3.3%, Al2O3: 31.5%, SiO2: 6.0%, C: ≤0.05%, P: ≤0.01%, and S: ≤0.03%.

[0071] The whole process of electroslag remelting adopts Ar gas protection, and the remelting rate is 7kg / min;

[0072] The specification after remelting is φ640*L, and annealing treatment is carried out after remelting out of the furnace.

[0073] S5 Forging

[0074] The steel ingot obtained by electroslag remelting was heated to 1210±20℃, kept warm for 4h before forging, with the initial forging temperature of 1187℃ and the final forging temperature of 883℃. The forging ratio was 13, and the size after forging was φ250*L.

[0075] Heat Treatment of S6 Bars

[0076] The heat treatment system is normalizing + quenching + tempering.

[0077] Normalizing: 920±10℃ for 4.5h, air cooling; normalizing can refine and even the matrix grains, making it easier to obtain equiaxed grains;

[0078] Quenching: 930±10℃ for 4.5h, oil cooling; quenching can make the austenite structure bypass the pearlite to form a C curve, and obtain the martensite structure to the maximum extent;

[0079] Tempering: Keep at 260±10℃ for 12h, then air cool after being taken out of the furnace; tempering can reduce the internal stress of martensitic structure and improve the toughness of the material.

[0080] The low-alloy high-hardenability ultra-high strength steel prepared in this embodiment has a tensile strength of 1637 MPa, a yield strength of 1356 MPa, an elongation of 13.5%, an impact energy of 77 J, a fracture toughness K1c of 115.3 MPa*m0.5, and a hardenability of J46-50 after corresponding tests.

[0081] Figure 1 To detect the test results of hardenability, the test method is in accordance with GB / T 225-2006: End quenching test method for hardenability of steel is Jominy test.

[0082] Example 2

[0083] A low alloy high hardenability ultra-high strength steel, the chemical composition of which is expressed in mass percentage:

[0084] C: 0.29%, Mn: 1.42%, Si: 1.54%, S: 0.001%, P: 0.0025%, Cr: 1.33%, Ni: 0.47%, Mo: 0.43%, V: 0.08%, Cu: 0.01%, Ti: 0.023%, B: 0.0022%, Al: 0.017%, and the balance is Fe.

[0085] The method for preparing the low-alloy high-hardenability ultra-high strength steel comprises the following steps:

[0086] S1 Electric Arc Furnace Melting

[0087] A. The charge is composed of carbon scrap steel and CrNiMo return steel, ferrochrome, ferronickel and ferromolybdenum, with a carbon content of 0.70%;

[0088] Before loading the furnace, 825 kg of lime is laid on the bottom of the furnace, and then scrap steel is loaded and sent for electric melting. The loading capacity is 33 t.

[0089] B. During the process of material smelting, 413kg of fluorite is added, the slag making amount is 3.75%, and the whole process is foam slag submerged arc operation, and slag flow operation is used. After full melting, it enters the oxidation period and oxygen is blown for dephosphorization.

[0090] C. Steel composition control: C: 0.080%, P: 0.001%, Cu≤0.10%. Steel tapping temperature is 1663℃.

[0091] S2 refining furnace smelting

[0092] A. When the electric arc furnace is tapped, 33kg of Al cake, 165kg of silicon-manganese alloy and 165kg of pre-melted slag are added.

[0093] The Ar flow rate during the steel connection process of the refining furnace is 85NL / min.

[0094] B. Lime and fluorite are also added to the refining furnace for slagging, 660kg of lime, of which lime: fluorite = 5:1, and the time is added after the steel is tapped;

[0095] Then add 66kg of C powder and 33kg of aluminum particles at one time and close the furnace door for diffusion and deoxidation.

[0096] C. After adding slag-making materials (pre-melted slag, lime, fluorite) and deoxidizer (carbon powder, aluminum particles), the temperature is quickly raised to 1637℃, and the slag is white before entering the refining period. The refining temperature is 1637℃, and the refining time is 45min. During the refining period, samples are taken for analysis of the components. According to the analysis results and wiring calculation, 8kg of carbon powder, 55kg of ferromanganese, 11kg of ferrosilicon, 31kg of ferrochrome, 5kg of ferronickel, 17kg of ferromolybdenum, 22kg of ferrovanadium, 3.5kg of sponge titanium, 1.7kg of ferroboron, and 1kg of aluminum particles are added.

[0097] D. The refining time is sufficient, the composition is qualified, the refining is completed, the temperature is raised to 1686℃, and the bag enters the vacuum degassing furnace.

[0098] S3 Vacuum Degassing

[0099] Vacuum degassing vacuum degree 34Pa, holding time 20min, Ar gas flow 37NL / min, vacuum is broken after holding time is sufficient. Temperature measurement 1562℃, hanging ladle pouring electrode: size φ530*L. After electrode pouring, mold cooling 12h, and demolding to obtain the electrode.

[0100] S4 Electroslag Remelting

[0101] After the oxide scale is removed from the electrode surface, electroslag remelting is performed. The amount of pre-melted slag is 180 kg, and the pre-melted slag composition is: CaF2: 37.5%, CaO: 21.7%, MgO: 3.3%, Al2O3: 31.5%, SiO2: 6.0%, C: ≤0.05%, P: ≤0.01%, S: ≤0.03%.

[0102] The whole process of electroslag remelting is protected by Ar gas, and the remelting rate is 7kg / min. The specification after remelting is φ640*L, and annealing treatment is carried out after remelting out of the furnace.

[0103] S5 Forging

[0104] The steel ingot is heated to 1210±20℃ and kept for 4 hours before forging, the initial forging temperature is 1165℃, and the final forging temperature is 867℃. The forging ratio is 13, and the size after forging is φ250*L.

[0105] Heat Treatment of S6 Bars

[0106] The heat treatment system is normalizing + quenching + tempering.

[0107] Normalizing: 920±10℃ for 4.5h, air cooling.

[0108] Quenching: 930±10℃ for 4.5h, oil cooling.

[0109] Tempering: keep at 260±10℃ for 12h, then air cool after leaving the furnace.

[0110] After the low alloy high hardenability ultra-high strength steel prepared in this embodiment is treated by this process, the tensile strength is 1682MPa, the yield strength is 1373MPa, the elongation is 12.0%, the impact energy is 74J, the fracture toughness K1c is 114.2MPa*m0.5, and the hardenability is J47-50.

[0111] Example 3

[0112] A low alloy high hardenability ultra-high strength steel, the chemical composition is as follows in mass percentage:

[0113] C: 0.32%, Mn: 1.44%, Si: 1.52%, S: 0.0010%, P: 0.0020%, Cr: 1.31%, Ni: 0.46%, Mo: 0.50%, V: 0.12%, Cu: 0.01%, Ti: 0.052%, B: 0.005%, Al: 0.045%, and the balance is Fe.

[0114] The method for preparing the low-alloy high-hardenability ultra-high strength steel comprises the following steps:

[0115] S1 Electric Arc Furnace Melting

[0116] A. The charge is composed of carbon scrap steel and CrNiMo return steel, ferrochrome, ferronickel and ferromolybdenum, with a carbon content of 0.70%. Before loading the furnace, 775kg of lime is laid on the bottom of the furnace to have a dephosphorization effect, and then the scrap steel is loaded and sent to the power melting, with a loading capacity of 31t.

[0117] B. During the process of material smelting, 388kg of fluorite is added, and the slag making amount is 3.75%. The whole process is foam slag submerged arc operation, and slag flow operation is used. After full melting, it enters the oxidation period, and oxygen is blown to remove phosphorus, aluminum and titanium.

[0118] C. Steel composition: C 0.07%, P 0.002%, Cu≤0.10%. Steel tapping temperature is 1659℃.

[0119] S2 refining furnace smelting

[0120] A. 31kg Al cake, 155kg silicon-manganese alloy and 155kg pre-melted slag are added during the steel tapping process of the electric arc furnace. The Ar flow rate during the steel tapping process of the refining furnace is 91NL / min.

[0121] B. Add slag-making materials into the refining furnace: 630kg lime, lime: fluorite = 5:1, and add it after the steel is tapped. Then add 62kg C powder, 62kg calcium carbide, and 31kg aluminum particles at one time, and close the furnace door for diffusion and deoxidation.

[0122] C. After adding slag-making materials and deoxidizers, the temperature is quickly raised to 1643℃, and the slag is white before entering the refining period. The refining temperature is 1643℃, and the refining time is 45min. During the refining period, samples are taken for component analysis. According to the analysis results and wiring calculation, 12.4kg of carbon powder, 24kg of ferromanganese, 50kg of ferrosilicon, 31kg of ferrochrome, 9kg of ferronickel, 23kg of ferromolybdenum, 21kg of ferrovanadium, 3.0kg of sponge titanium, and 1.3kg of ferroboron are added.

[0123] D. The refining time is sufficient, the composition is qualified, the refining is completed, the temperature is raised to 1681℃, and the bag enters the vacuum degassing furnace.

[0124] S3 Vacuum Degassing

[0125] Vacuum degassing vacuum degree 31Pa, holding time 20min, Ar gas flow 31NL / min, vacuum is broken after holding time is sufficient. Temperature measurement 1566℃, hanging ladle pouring electrode: size φ530*L. After electrode pouring, mold cooling 12h, and demolding to obtain the electrode.

[0126] S4 Electroslag Remelting

[0127] After removing the oxide skin from the electrode surface, electroslag remelting is performed. The amount of pre-melted slag is 180kg, and the pre-melted slag composition is: CaF2: 37.5%, CaO: 21.7%, MgO: 3.3%, Al2O3: 31.5%, SiO2: 6.0%, C: ≤0.05%, P: ≤0.01%, S: ≤0.03%. Ar gas protection is used throughout the electroslag remelting process, and the remelting rate is 7kg / min. The specification after remelting is φ640*L, and annealing treatment is performed after remelting out of the furnace.

[0128] S5 Forging

[0129] The steel ingot is heated to 1210±20℃ and kept for 4h before forging, the initial forging temperature is 1182℃, and the final forging temperature is 851℃. The forging ratio is 12, and the size after forging is φ250*L.

[0130] Heat Treatment of S6 Bars

[0131] The heat treatment system is normalizing + quenching + tempering.

[0132] Normalizing: 920±10℃ for 4.5h, air cooling.

[0133] Quenching: 930±10℃ for 4.5h, oil cooling.

[0134] Tempering: keep at 260±10℃ for 12h, then air cool after leaving the furnace.

[0135] After the low alloy high hardenability ultra-high strength steel prepared in this embodiment is treated by this process, the tensile strength is 1671MPa, the yield strength is 1354MPa, the elongation is 13.0%, the impact energy is 75J, the fracture toughness K1c is 112.1MPa*m0.5, and the hardenability is J48-50.

[0136] Example 4

[0137] A low alloy high hardenability ultra-high strength steel, the chemical composition is as follows in mass percentage:

[0138] C: 0.31%, Mn%: 1.42%, Si: 1.30%, S: 0.0014%, P: 0.0023%, Cr: 1.31%, Ni: 0.44%, Mo: 0.49%, V: 0.12%, Cu: 0.01%, Ti: 0.042%, B: 0.003%, Al: 0.060%, and the balance is Fe.

[0139] The method for preparing the low-alloy high-hardenability ultra-high strength steel comprises the following steps:

[0140] S1 Electric Arc Furnace Melting

[0141] A. The charge is composed of carbon scrap steel and CrNiMo return steel, ferrochrome, ferronickel and ferromolybdenum, with a carbon content of 0.70%. Before loading the furnace, 750kg of lime is laid on the bottom of the furnace to have a dephosphorization effect, and then the scrap steel is loaded and sent to the power melting, with a loading capacity of 30t.

[0142] B. During the process of material smelting, 375kg of fluorite is added, and the slag making amount is 3.75%. The whole process is foam slag submerged arc operation, and slag flow operation is used. After full melting, it enters the oxidation period, and oxygen is blown to remove phosphorus, aluminum and titanium.

[0143] C. Steel composition: C 0.09%, P 0.001%, Cu≤0.10%. Steel tapping temperature is 1662℃.

[0144] S2 refining furnace smelting

[0145] A. During the steel tapping process of the electric arc furnace, 30kg Al cake, 150kg silicon-manganese alloy and 150kg pre-melted slag are added. During the steel tapping process of the refining furnace, the Ar flow rate is 92NL / min.

[0146] B. Add slag-making materials into the refining furnace: 600kg lime, lime: fluorite = 5:1, and add it after the steel is tapped. Then add 60kg C powder, 60kg calcium carbide, and 30kg aluminum particles at one time, close the furnace door for diffusion deoxidation.

[0147] C. After adding slag-making materials and deoxidizers, the temperature is quickly raised to 1645℃, and the slag is white before entering the refining period. The refining temperature is 1645℃, and the refining time is 45min. During the refining period, samples are taken for component analysis. According to the analysis results and wiring calculation, 5kg of carbon powder, 47kg of ferromanganese, 25kg of ferrosilicon, 8kg of ferrochrome, 19kg of ferronickel, 14kg of ferromolybdenum, 27kg of ferrovanadium, 2.9kg of sponge titanium, 1.5kg of ferroboron, and 1.2kg of aluminum particles are added.

[0148] D. The refining time is sufficient, the composition is qualified, the refining is completed, the temperature is raised to 1687℃, and the bag enters the vacuum degassing furnace.

[0149] S3 Vacuum Degassing

[0150] Vacuum degassing vacuum degree 35Pa, holding time 20min, Ar gas flow 38NL / min, vacuum is broken after holding time is sufficient. Temperature measurement 1568℃, hanging ladle pouring electrode: size φ530*L. After electrode pouring, mold cooling 12h, and electrode is obtained after demoulding.

[0151] S4 Electroslag Remelting

[0152] After removing the oxide skin from the electrode surface, electroslag remelting is performed. The amount of pre-melted slag is 180kg, and the pre-melted slag composition is: CaF2: 37.5%, CaO: 21.7%, MgO: 3.3%, Al2O3: 31.5%, SiO2: 6.0%, C: ≤0.05%, P: ≤0.01%, S: ≤0.03%. Ar gas protection is used throughout the electroslag remelting process, and the remelting rate is 7kg / min. The specification after remelting is φ640*L, and annealing treatment is performed after remelting out of the furnace.

[0153] S5 Forging

[0154] The steel ingot is heated to 1210±20℃ and kept for 4h before forging, the initial forging temperature is 1177℃, and the final forging temperature is 866℃. The forging ratio is 13, and the size after forging is φ250*L.

[0155] Heat Treatment of S6 Bars

[0156] The heat treatment system is normalizing + quenching + tempering.

[0157] Normalizing: 920±10℃ for 4.5h, air cooling.

[0158] Quenching: 930±10℃ for 4.5h, oil cooling.

[0159] Tempering: keep at 260±10℃ for 12h, then air cool after leaving the furnace.

[0160] The low-alloy high-hardenability ultra-high strength steel prepared in this embodiment has a tensile strength of 1623 MPa, a yield strength of 1334 MPa, an elongation of 13.5%, an impact energy of 68 J, a fracture toughness K1c of 120.9 MPa*m0.5, and a hardenability of J48-50.

[0161] The grain size test results of the ultra-high strength steel of the present invention are as follows: Figure 2 As shown, the test result is 6.5; the present invention refines the grain size, increases strength and toughness; and through reasonable process, reduces the inclusion content, inclusion detection Figure 3 As shown, the results show that class B is 0.5 level fine, class D is 0.5 level fine, and the rest are 0 level.

[0162] The low-alloy high-hardenability ultra-high-strength steel provided by the present invention has a high-strength steel tensile strength Rm≥1600MPa, a yield strength Rp0.2≥1300MPa, an elongation A≥10%, an impact energy Aku≥50J, a fracture toughness K1c≥110MPa*m0.5, and a hardenability ≥J46-50. It is a low-alloy, low-cost, high-hardenability ultra-high-strength steel; the ultra-high-strength steel can be used not only as a civilian structural material, but also in military applications.

[0163] The above embodiments are preferred examples for implementing the present invention, and the present invention is not limited to the above embodiments. Any non-essential additions and substitutions made by those skilled in the art based on the technical features of the technical solution of the present invention shall fall within the protection scope of the present invention.

Claims

1. A low alloy high hardenability ultra-high strength steel, characterized in that: In terms of mass percentage, its chemical composition is: C: 0.29~0.33%, Mn: 1.30~1.60%, Si: 1.30~1.60%, Cr: 1.10~1.40%, Ni: 0.40~0.50%, Mo: 0.30~0.50%, V: 0.08~0.15%, Cu: ≤0.20%, Ti: 0.02~0.06%, B: 0.001~0.005%, Al: 0.01~0.06%, S: ≤0.0060%, P: ≤0.013%, and the balance is Fe.

2. The low alloy high hardenability ultra-high strength steel according to claim 1, characterized in that: In terms of mass percentage, its chemical composition is: C: 0.29~0.30%, Mn: 1.30~1.60%, Si: 1.36~1.60%, Cr: 1.24~1.40%, Ni: 0.45~0.50%, Mo: 0.30~0.46%, V: 0.08~0.15%, Cu: ≤0.20%, Ti: 0.02~0.041%, B: 0.001~0.0027%, Al: 0.02~0.06%, S: ≤0.0060%, P: ≤0.013%, and the balance is Fe.

3. The low alloy high hardenability ultra-high strength steel according to claim 1, characterized in that: In terms of mass percentage, its chemical composition is: C: 0.29~0.33%, Mn: 1.30~1.42%, Si: 1.30~1.54%, Cr: 1.10~1.33%, Ni: 0.40~0.47%, Mo: 0.43~0.50%, V: 0.08~0.10%, Cu: ≤0.20%, Ti: 0.023~0.06%, B: 0.003~0.005%, Al: 0.01~0.06%, S: ≤0.0060%, P: ≤0.013%, and the balance is Fe.

4. The low alloy high hardenability ultra-high strength steel according to claim 1, characterized in that: In terms of mass percentage, its chemical composition is: C: 0.31~0.33%, Mn: 1.44~1.60%, C: 0.29~0.33%, Mn: 1.30~1.42%, Si: 1.40~1.52%, Cr: 1.20~1.31%, Ni: 0.40~0.46%, Mo: 0.43~0.50%, V: 0.08~0.12%, Cu: ≤0.20%, Ti: 0.042~0.052%, B: 0.001~0.003%, Al: 0.01~0.06%, S: ≤0.0060%, P: ≤0.013%, and the balance is Fe.

5. A method for preparing the low alloy high hardenability ultra-high strength steel according to claim 1, characterized in that: The following operations are included: S1 Electric Arc Furnace Melting Before charging, lime is laid on the bottom of the electric arc furnace, and then the charge is loaded; the charge includes carbon steel, ferrochrome, ferronickel and ferromolybdenum, with a carbon content of ≥0.6%; After the furnace is loaded, it is sent to electric melting. Fluorite is added to make slag during the material smelting process. The whole process is to make foam slag and submerged arc operation, and the slag flow operation is adopted to ensure that the slag volume in the furnace is 3-5%; after full melting, it enters the oxidation period and oxygen is blown for dephosphorization; The temperature of the smelting process is controlled between 1550 and 1670°C, the current is ≤60000A, and the smelting time is 2 to 4 hours; After smelting, the steel is tapped at a temperature of 1650-1670°C. In terms of mass fraction, the steel composition requirements are: C≤0.1%, P≤0.002%, Cu≤0.10%; S2 refining furnace smelting When the electric arc furnace is tapped to the refining furnace, Al material, ferromanganese, ferrosilicon, pre-melted slag are added along the flow, and then slag-making materials are added; Ar protection is used during the steel connection process of the refining furnace, and the flow rate is ≥80NL / min; Then add C powder and aluminum particles for deoxidation at one time, close the furnace door; then quickly raise the temperature to above 1620℃, and enter the refining stage after the slag turns white; The refining temperature is 1620-1650°C, and the refining time is not less than 40 minutes. During the refining period, samples are taken for component analysis, and ferromolybdenum, ferrovanadium, ferroboron and materials required to make up the components are added according to the analysis results, and the Ar gas stirring is maintained at 30-50NL / min. When the refining time is sufficient and the composition is qualified, the refining is completed. After the temperature is raised to 1670-1700℃, the bag enters the vacuum degassing furnace; S3 Vacuum Degassing The vacuum degree of vacuum degassing is ≤67Pa, the pressure holding time is not less than 20min, the Ar gas flow rate is controlled at 10~40NL / min, and the vacuum can be broken after the pressure holding time is sufficient; When the temperature is controlled to 1560-1580℃, the ladle is hung to cast the electrode; After the electrode is cast, the mold is cooled, and after the mold is cooled for 12 hours, the electrode is demoulded to obtain the electrode; S4 Electroslag Remelting After the oxide skin is removed from the electrode surface, the electrode is electroslag remelted. The amount of pre-melted slag is 3-5% by mass ratio. Ar gas protection is used throughout the electroslag remelting process. The remelting rate is 5-7kg / min. After the electrode is remelted, it is annealed. S5 Forging The steel ingot obtained by electroslag remelting is heated at 1190-1230°C for 2-4 hours, and then forged after being taken out of the furnace; The forging ratio is required to be no less than 7, the initial forging temperature is ≥1120℃, and the final forging temperature is ≥850℃. S6 Heat Treatment After forging, the heat treatment system of normalizing, quenching and tempering is carried out in sequence; during normalizing, the temperature is 920±10℃, kept warm for 3~5h and then air-cooled; during quenching, the temperature is 930±10℃, kept warm for 3~5h and then oil-cooled; during tempering, the temperature is 260±10℃, kept warm for 2~10h and then air-cooled.

6. The method for preparing low alloy high hardenability ultra-high strength steel according to claim 5, characterized in that: The furnace charge includes carbon scrap steel CrNiMo return steel, ferrochrome, ferronickel and ferromolybdenum, and the carbon content is 0.70% of the furnace charge mass; the lime paved on the furnace bottom is 0.020-0.030% of the furnace charge mass.

7. The method for preparing low alloy high hardenability ultra-high strength steel according to claim 5, characterized in that: During smelting in the refining furnace, the slag-making materials include pre-melted slag, lime and fluorite; in terms of mass ratio, the amount of pre-melted slag is 1.0-1.60% of the molten steel, the amount of lime is 1.0-1.50% of the molten steel, and the ratio of lime to fluorite is 4-5:1.

Citation Information

Patent Citations

  • High-plasticity-toughness low-alloy ultrahigh-strength steel and preparation method

    CN111979487A

  • High-hardenability 35SiMnCrMoB steel for wear-resistant parts of engineering machinery and manufacturing method of high-hardenability 35SiMnCrMoB steel

    CN114134430A

  • Low-cost low-alloy ultrahigh-strength steel and manufacturing method thereof

    CN114774630A

  • Production method for high-strength steel plate for engineering machinery

    WO2023029282A1

Cited By

  • Hob steel for rock stratum ground excavator and preparation method

    CN120311185A

  • A kind of rock ground excavator cutter steel and preparation method

    CN120311185B